KEBIJAKAN PENGEMBANGAN INFRASTRUKTUR DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI DI MERAUKE - Beatus Tambaip; Alexander Phuk Tjilen; Yosephina Ohoiwutun (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2023)
The purpose of this study is to analyze infrastructure development policies on economic growth in Merauke district. The research method used by researchers in this study is a qualitative research method with a descriptive approach. The research location taken was in Merauke Regency. In collecting data, researchers used data collection techniques which were carried out by interview, observation, and documentation methods. The data analysis method used in this study is the interactive analytical method. The results of the study show that infrastructure improvements can also encourage the development of certain economic sectors, such as the manufacturing industry, tourism and the energy sector. In addition, infrastructure development can also create new jobs and improve people's welfare. Infrastructure development policies can have a significant impact on economic growth.